The role of sleep-related breathing disorders in patients with heart failure. Review of the article - M. V. Agaltsov (Российский кардиологический журнал)
Review of the article Medvedeva E. A., Korostovtseva L. S., Bochkarev M. V., Sazonova Yu. V., Sviryaev Yu. V. Clinical and prognostic role of sleep-related breathing disorders in patients with heart failure depending on body mass index. Russian Journal of Cardiology. 2023;28(3):5263. doi:10.15829/1560-4071-2023-5263. EDN LWBNSN